KARAKTERISTIK NUGGET TAHU DENGAN PENAMBAHAN JAMUR TIRAM (Pleurotus ostreatus) DAN PERBEDAAN JENIS MINYAK UNTUK MENGGORENG - Titri Siratantri Mastuti (Universitas Pelita Harapan, 2021)
Nugget is a fried processed product with basic ingredients generally from chicken or fish. Nugget can also be made from plant-based ingredients such as high protein white tofu and white oyster mushrooms. The cooking oil used can affect the fat content of the nuggets. The purpose of this study was to determine the best ratio of white tofu and white oyster mushrooms, the right type of binder flour, to determine the right concentration of binder flour and to determine the right type of oil for frying tofu nuggets which have the best characteristics. The first phase of research consisted of two factors, namely the type of flour as a binding agent (wheat flour, sago flour and wheat flour: sago flour) with a concentration of 10% and the ratio of white tofu: white oyster mushrooms (100: 0, 90:10, 80: 20, 70:30). The second phase of the research consisted of two factors, namely the concentration of selected flour in stage I (15%, 20%, 25%) and the type of oil (palm oil and coconut oil) used for frying tofu nuggets. The parameters analyzed included moisture content, ash content, protein content, fat content, carbohydrate content, color, texture, and organoleptics (multiple paired comparison and hedonic). The best formulation of tofu nuggets is nuggets with the 15% wheat flour as binder with ratio of white tofu: white oyster mushrooms (90:10) and fried using coconut oil. The best tofu nuggets have a water content of 27.42%, a protein content of 16.90%, a fat content of 17.48%. The physical characteristics of tofu nuggets are yellowish brown on the outside, and have a compact and chewy texture.Keywords : nugget, tofu, white oyster mushrooms, wheat, coconut oil